Infantile myofibromatosis and capillary malformation of the skin due to PDGFRB mosaicism - Pudig, Luise; Lassmann, Silke; Jacob, Sebastian; Nastainczyk-Wulf, Marina; Haak, Anja; Werner, Martin; Kapp, Friedrich G; Hettmer, Simone (Molecular and cellular pediatrics, 2025)
This report describes the case of a 25-year-old female patient with multicentric infantile myofibromatosis since early infancy, superficial capillary malformations and congenital hypoplasia of the third and fourth finger of her right hand. All known lesions were located in the upper extremities, the chest and the upper back. A pathogenic, gain-of-function platelet-derived growth factor receptor-beta ( PDGFRB) variant (p.N666K, c.1998 C > A) was detected in two myofibromas and in a capillary malformation on the upper back, but not in DNA obtained from blood mononuclear cells. Thus, PDGFRB mosaicism appears to account for the patient’s myofibromas and capillary malformations, supporting a broad spectrum of PDGFRB -driven anomalies ranging from myofibromas to vascular malformations.